Improved heat stability of recombined evaporated milk emulsions by wet heat pretreatment of skim milk powder dispersions. (September 2021) - Wu, Jianfeng; Chen, Simin; Wang, Teng; Li, Hao; Sedaghat Doost, Ali; Van Damme, Els J.M.; De Meulenaer, Bruno; Van der Meeren, Paul
Abstract: In this study, skim milk powder (SMP) aqueous dispersions were subjected to a preliminary wet heat incubation at various temperatures (70–90 °C) to improve the heat stability of recombined filled evaporated milk (RFEM) emulsions. The determination of the free amino group and free lactose content and SDS-PAGE revealed that both whey proteins and caseins were involved in the conjugation with lactose upon preliminary wet heating at different temperatures. The results of the non-sedimentable serum protein content, the particle size and relative viscosity of the SMP dispersion indicated that both association of whey proteins with casein micelles and casein dissociation from the micelles occurred during the incubation. The heat stability of the subsequently produced RFEM emulsions was greatly enhanced: RFEM emulsions could withstand a typical in-container sterilization procedure (i.e. 30 min of heating at 120 °C) without coagulation (D4, 3 <5 μm and consistency coefficient <50 mPa s) when selecting an appropriate incubation time. Generally, the higher the incubation temperature, the shorter the incubation time needed to enable a heat-stable RFEM emulsion. However, prolonged incubation had a negative effect on the heat stability of RFEM emulsions, and a narrower incubation time interval that enabled an improved heat stability was observed at a higher incubation temperature. Graphical abstract: Image 1 Highlights: Wet heating of SMP dispersions gave rise to the formation of conjugates of milk proteins and lactose. Pre-heated SMP-stabilized REM emulsions could withstand at least 30min of heating at 120 °C without coagulation. The higher the incubation temperature, the shorter the incubation time needed to enable a heat-stable REM. Prolonged incubation had a devastating effect on the heat stability of REM. A narrower incubation time interval that enabled an improved heat stability of REM.